DEVELOPMENT OF SCIENTIFIC COMPETENCE OF STUDENTS ON THE TOPIC «GENETIC RELATIONSHIPS OF THE MAIN CLASSES OF INORGANIC COMPOUNDS» IN THE SECONDARY SCHOOL CHEMISTRY COURSE - Umarov, Saidanvar; Sirojov, Farhod (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The main task of teaching this topic is to teach students the ways and methods of obtaining the basic classes of inorganic compounds and genetic bonds of these classes through various methods and techniques of teaching chemistry and to increase the level of knowledge of students in chemistry.